2021
DOI: 10.1155/2021/6661272
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Multicriteria Decision Support System and Industrial Internet of Things for Source Code Transformation

Abstract: The large scale increase of communication and number of devices in the Industrial Internet of Things (IIoT) has rapidly enabled practitioners to make decisions based on multicriteria. Multicriteria decision support systems (MCDSSs) play an important role in decision-making for a particular situation based on several criteria. Making of decision based on multicriteria is the main issues for research community and practitioners of the IIoT. Several decision support systems (DSSs) are offered for making decisions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Aiming at the inability of the evaluation framework to deal with complex fuzzy indicators, Huang proposed the fuzzy layering theory from the perspective of the Internet of ings for the first time by measuring the evaluation indicators of teaching quality [13]. Multi-criteria-based decision-making is a major problem facing the IIoT research community and practitioners, and Hao et al provided several decision support systems to make decisions that have the potential to support the activities of the decision-making process [14]. Although many people have done a lot of research on the Internet of ings algorithm and decisionmaking risk style, few people have introduced these two into the research on the path of rural revitalization and the rule of law.…”
Section: Introductionmentioning
confidence: 99%
“…Aiming at the inability of the evaluation framework to deal with complex fuzzy indicators, Huang proposed the fuzzy layering theory from the perspective of the Internet of ings for the first time by measuring the evaluation indicators of teaching quality [13]. Multi-criteria-based decision-making is a major problem facing the IIoT research community and practitioners, and Hao et al provided several decision support systems to make decisions that have the potential to support the activities of the decision-making process [14]. Although many people have done a lot of research on the Internet of ings algorithm and decisionmaking risk style, few people have introduced these two into the research on the path of rural revitalization and the rule of law.…”
Section: Introductionmentioning
confidence: 99%
“…However, they did not consider the security and fault-tolerance of the applications. Fault-tolerant aware SOA is discussed in [2]. The goal was to minimize the failure risks and exploit the primary backup method to handle any SOA architecture failure.…”
Section: Related Workmentioning
confidence: 99%
“…Real world applications of the digital transformation of technologies such as the Industrial Internet of Things (IIoT) posses many advantages [1]. Such applications belong to the eagriculture, e-healthcare, e-transport, e-servicing, and augmented fields [2]. Cloud computing is an incipient archetype which offers services based on Service-Oriented Architecture (SOA) [3].…”
Section: Introductionmentioning
confidence: 99%
“…Results have showed that orientation policy of the USA tends to favor demandside policy, political and education, public services, and training policies are favored, whereas policy preferences, public services, technical, scientific development and political favored by Germany and environmental-side policy, political, legal and regulatory, and public service policies by China [44]. Various other approaches have been suggested in the literature in the area of IoT [45,46].…”
Section: Cyber-security and Industry Researches Have Been Donementioning
confidence: 99%